Shaking and Weight of the Blood Bag - Amueleh, Ahmed Hassan Mahdi; El-Sada, Abbas Ajil Alwan Abd; Fleeh, Shams Alduha Dawood; Maktoof, Ahmed Majeed (American Journal of Botany and Bioengineering, 2025)
The blood bag shaking machine is an important device in blood donation process. Usually, when the blood flows out of the body, it is clotted. Thus, it is necessary to shake the blood in the bag with anti-clot solution and many factors which affect blood quality. The shaking machine for blood donation process is imported and expensive. This paper presents the design of a shaking machine for shaking the blood bag and volume estimation without sensor. The amount of blood in the bag is related to load torque on the vibration motor . The volume of the blood bag increases in blood donation process until the desired volume, which the current increases too. The current and load torque can be used to estimate volume of the blood bag and blood flow rate at the same time via the principles of closedloop speed control system, observer and adaptive compensator.